Successful Treatment of Early-Stage Jejunum Adenocarcinoma by Endoscopic Mucosal Resection Using Double-Balloon Endoscopy: A Case Report. (10th July 2012) - Suzuki, Hirobumi; Yamada, Atsuo; Watabe, Hirotsugu; Kobayashi, Yuka; Hirata, Yoshihiro; Yamaji, Yutaka; Yoshida, Haruhiko; Koike, Kazuhiko
Abstract : Small bowel adenocarcinoma (SBA) has generally been considered to have a poor prognosis because of nonspecific presentations and difficulties in detection of the disease. The advent of capsule endoscopy (CE) and double-balloon endoscopy (DBE) makes it possible to access to the small intestine for endoscopic interventions. We describe a successful case of early jejunum adenocarcinoma completely resected by endoscopic mucosal resection (EMR) using double-balloon endoscopy (DBE). Early diagnosis and EMR using new technologies such as CE and DBE may improve the recognition of this disease that, at present, has a poor prognosis.